New Results on Controllability Analysis for Sobolev-Type Volterra-Fredholm Functional Integro-Differential Equation in Banach Space - Kaliraj, K.; Thilakraj, E.; Ravichandran, C. (Discontinuity, Nonlinearity, and Complexity, 2026)
This manuscript analyses the controllability of a certain classes of sobolev-type Volterra-Fredholm functional Integro-Differential Equations (SVFIDE) of fractional order via Caputo fractional derivative involving finite delay with initial condition. We have empolyed the precompactness of Arzela-Ascoli theorem along with the standard fixed point method to attain the desired result. Finally, we present an example to demonstrate the validity of our result.